﻿Comparative assessment of clinical trials, indications, pharmacokinetic parameters and side effects of approved platinum drugs - Stefka Ivanova (Pensoft Publishers, 2022)
Platinum complexes are among the most commonly applied anticancer agents. The aim of current work is collection, analysing and comparative estimation of clinical trials and pharmacological indications of currently approved for application platinum detivatives: Cisplatin, Carboplatin, Oxaliplatin, Nedaplatin (Japan), Lobaplatin (China), Heptaplatin (North Korea), and Satraplatin. The other aim of the study includes the summarizing of the hystoric data for the stages of the developlement of these drugs, and the comparison of pharmacokimetic parameters, side effecs and the dose-liniting factors of the drugs. The observational study on pharmacokinetic parameters shows that protein binding decreases in order: 95% (Cisplatn); 90% (Oxaliplatin); 50% (Nedaplatin); low (Carboplatin). For every of Cisplatin, Carboplatin, Oxaliplatin have been reported more than 1000 clinical trials; for Lobaplatin, Nedaplatin, Satraplatin - about 10 trials. The differenses in dose-limiting effects are: neuro-, nephro-, ototoxicity (Cisplatin); neurotoxicity (Oxaliplatin); nephrotoxicity (Heptaplatin); myelosuppression: thrombocytopenia, neutropenia, leukopenia (Carboplatin, Nedaplatin, Satraplatin).